PATIENTS’ ILLNESS PERCEPTIONS OF RHEUMATOID ARTHRITIS BASED ON THE BIPQ QUESTIONNAIRE AT HANOI MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Patients’ perception of rheumatoid arthritis plays a crucial role in the treatment process, directly affecting adherence and the effectiveness of interventions.Objective: To assess patients’ perceptions of rheumatoid arthritis using the Brief Illness Perception Questionnaire (BIPQ) and to analyze several related factors.Subjects and Methods: A cross-sectional descriptive study was conducted on 149 patients with rheumatoid arthritis diagnosed according to the ACR/EULAR 2010 criteria from September 2024 to August 2025, who were examined and treated at Hanoi Medical University Hospital. The Brief Illness Perception Questionnaire (BIPQ) was used to assess illness perception, with higher total scores reflecting a more negative perception of the disease.Results: The mean BIPQ score was 44.88 ± 7.44, corresponding to a moderate level of negative illness perception. The proportion of patients with moderate to high negative perceptions was 74.5%. Patients under 55 years of age (OR 3.93), those with moderate or severe VAS pain (OR 7.1), and those with treatment costs exceeding 2 million VND per month (OR 4.93) were independently associated with a high level of negative perception.Conclusion: Patients with rheumatoid arthritis had a moderate level of negative illness perception. Interventions should focus on improving illness perception, particularly among patients under 55 years old, strengthening pain management, and reducing treatment costs to help alleviate anxiety, enhance treatment adherence, and improve quality of life
Keywords: Rheumatoid arthritis, Illness perception, Brief Illness Perception Questionnaire (BIPQ), Hanoi Medical University Hospital